Determining bioavailability of food folates in a controlled intervention study - MOLLOY, ANNE MARIE; SCOTT, JOHN MARTIN (My University, 2004)
Background: The concept of dietary folate equivalents (DFEs) in the United States recognizes the differences in bioavailability between natural food folates and the synthetic vitamin, folic acid. However, many published reports on folate bioavailability are problematic because of several confounding factors. Objective: We compared the bioavailability of food folates with that of folic acid under controlled conditions. To broadly represent the extent to which natural folates are conjugated in foods, we used 2 natural sources of folate, spinach (50% polyglutamyl folate) and yeast (100% polyglutamyl folate). Design: Ninety-six men were randomly assigned according to their screening plasma homocysteine (tHcy) concentration to 1 of 4 treatment groups for an intervention period of 30 d. Each subject received (daily under supervision) either a folate-depleted "carrier" meal or a drink plus 1) placebo tablet, 2) 200 ?g folic acid in a tablet, 3) 200 ?g natural folate provided as spinach, or 4) 200 ?g natural folate provided as yeast. Results: Among the subjects who completed the intervention, responses (increase in serum folate, lowering of tHcy) relative to those in the placebo group (n = 18) were significant in the folic acid group (n = 18) but not in the yeast folate (n = 19) or the spinach folate (n = 18) groups. Both natural sources of folate were significantly less bioavailable than was folic acid. Overall estimations of folate bioavailability relative to that of folic acid were found to be between 30% (spinach) and 59% (yeast). Conclusion: Relative bioavailability estimates were consistent with the estimates from the metabolic study that were used as a basis to derive the US DFE value.
PUBLISHED
PubMed ID: 15447898
Keywords: Food folate ? bioavailability ? homocysteine ? folic acid